Mataram Islam and Religiosity in Novel Trilogi Rara Mendut By YB. Mangunwijaya - Irsasri Irsasri; St. Y. Slamet; Retno Winarni; E. Nugraheni Eko Wardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2018)
Trilogy novel, Rara Mendut is one of the historical evident in fictional-historical novel which reveals reality in fictional expression. Rara Mendut tells the main character, woman with strong and struggle oriented in gaining her goals. The struggle and principle of life dominated the story through its episodes compiling by the author, Y.B. Mangunwijaya. This research aims to dig up the principle of life, condition, and belief of people in Mataram Islam through the presentation of main character, Rara Mendut, Genduk Duku, and Lusi Lindri. Sociological approach and theory of sociology are used as theoretical framework to result the goal of the research. The result shows that in people of Mataram Islam had belief and perfoemed islam rules as the religion spred by Wali in Java island. The attitude and characters of Rara Mendut shows the values of Islamic teaching in the background of Matara Islam in novel Rara Mendut.